Determinants Affecting The Utilization of Instagram as A Promotional Tool Among Internal Medicine Patients at TK IV Cijantung Hospital, Kesdam Jaya - Sofi Muthia Yusridana; Yuli Prapanca Satar; Ahdun Trigono (International Journal of Health Engineering and Technology, 2026)
This study aims to analyze the determinants influencing the utilization of Instagram as a promotional medium among internal medicine patients at Tk IV Cijantung Kesdam Jaya Hospital, including the description of determinants, their relationships, and the most dominant influencing factor. This research employed a quantitative design with a survey approach. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in 92 respondents from the outpatient clinic, plus an additional 30 respondents for validity testing. Data analysis was performed using the Chi-Square test to examine variable relationships and further analysis to identify the dominant factor. The findings revealed that use of social media, content quality, posting frequency, consistency, and the factor of social media usage had a significant relationship with the utilization of Instagram as a promotional medium. The dominant influencing factor was use of social media, content quality, particularly informative, clear, and relevant content that addressed patient needs. The utilization of Instagram as a promotional tool at Tk IV Cijantung Kesdam Jaya Hospital can be optimized by improving content quality, managing posting frequency, ensuring consistency in information delivery, and encouraging patient engagement in social media usage. These results are expected to provide strategic input for hospital management in strengthening digital promotion strategies to enhance service quality and increase patient visits.